2015
DOI: 10.5455/ijmsph.2015.01052015333
|View full text |Cite
|
Sign up to set email alerts
|

Impact of educational intervention regarding mosquito-borne diseases and their control measures among multipurpose health workers (MPHWs) of Patan district, Gujarat, India

Abstract: Background: In rural areas, multipurpose health workers (MPHWs) play a key role in implementing control measures and behavior change communication at community level to prevent and control mosquito-borne diseases. Objective: To assess the knowledge of MPHWs regarding mosquito-borne diseases and control measures before and after single educational interventional training. Materials and Methods: This interventional study was conducted among purposively selected 100 MPHWs of Patan district, Gujarat, India, from J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 0 publications
0
16
2
Order By: Relevance
“…The mean score was 5.6 (SD 2.85), indicating some knowledge, but a lack of in-depth understanding [ 30 ]. General knowledge on mosquito borne diseases in India among a group of health-care workers was 83% ( n = 100) [ 31 ] whereas in a different study 88.1% ( n = 119) [ 32 ] of the general population sample was considered to have general knowledge.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The mean score was 5.6 (SD 2.85), indicating some knowledge, but a lack of in-depth understanding [ 30 ]. General knowledge on mosquito borne diseases in India among a group of health-care workers was 83% ( n = 100) [ 31 ] whereas in a different study 88.1% ( n = 119) [ 32 ] of the general population sample was considered to have general knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies measured knowledge of chikungunya [ 22 , 30 , 31 , 34 , 35 ] and mosquito borne disease [ 29 , 36 , 37 ] symptoms among populations affected by the disease. Knowledge of the signs and symptoms of chikungunya varied across different study populations; however, joint pain, fever, and swelling were commonly identified [ 22 , 30 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations